Proteomics and the Trypanosoma brucei cytoskeleton: advances and opportunities. - Portman, N; Gull, K (2012)
Trypanosoma brucei is the etiological agent of devastating parasitic disease in humans and livestock in sub-saharan Africa. The pathogenicity and growth of the parasite are intimately linked to its shape and form. This is in turn derived from a highly ordered microtubule cytoskeleton that forms a tightly arrayed cage directly beneath the pellicular membrane and numerous other cytoskeletal structures such as the flagellum. The parasite undergoes extreme changes in cellular morphology during its life cycle and cell cycles which require a high level of integration and coordination of cytoskeletal processes. In this review we will discuss the role that proteomics techniques have had in advancing our understanding of the molecular composition of the cytoskeleton and its functions. We then consider future opportunities for the application of these techniques in terms of addressing some of the unanswered questions of trypanosome cytoskeletal cell biology with particular focus on the differences in the composition and organisation of the cytoskeleton through the trypanosome life-cycle.